Input-output efficiency of 20 independent research teams at State Key Laboratory of Respiratory Disease 2009–2016: managerial implications for elsewhere in China - Bao, Rui; Zhuang, Hai-Shang; Peng, Wei; Li, Ming; Li, Kai-Ping; Zhou, Lin; Liu, Tian-Qiang; Wang, Xin-Wang (Journal of Thoracic Disease, 2018)
Currently, China’s State Key Laboratories (SKLs) play a vital role in the trend of scientific innovation in this amazing country. Specifically, SKLs as essential bases for national high-level research and talent training, are crucial in improving the country’s independent innovation capacity, core competitiveness, scientific and technical breakthrough, thereby leading China from a manufacturing to an innovating power. In this setting, analysis of the scientific input-output efficiency (IOE) may offer suggestion for decision-making in terms of funds optimization and management. An objective and reasonable approach of such analysis so far remains challenging, in light of so many factors associated with the scientific input-output issues. This can be shown in a recent attempt to look at the IOE of 20 independent research teams in State Key Laboratory of Respiratory Disease (SKLRD).